Religion and politics: A study on political attitudes of debout Muslims and the role of the Kyai in contemporary Java - Turmundi, Endang (Southeast Asian journal of social science, 1995)
Focusing on voting behavior (the support given to a political party in general elections), the author examines the relationship between the religious affiliation of Muslim society in Java and their political actions. He stresses the impact of ideas on socio-political action and inquires why Muslims give support to one political party and not to others. (DÜI-Sen)